Pilot study for irrigation modelling of a pear plantation - Tamás, J.; Fórián, T.; Nagy, A.; Nyéki, J.; Soltész, M.; Szabó, Z. (International Journal of Horticultural Science, 2010)
Our investigation was carried out in the area of Fruit growing Research and Consultant non-profit company, at Újfehértó. The pear requires large water quantity, but this pear plantation hasn’t irrigation system not yet. This study reviews the drainage conditions of the area based on digital elevation model, and examined the canopy cover of pear trees by evaluating of the hyperspectral image. Our aims were to determine the exact watershed based irrigation modelling and determining of the canopy% of the pear orchard to facilitate a precision irrigation decision support system.